2018
DOI: 10.1016/j.clinbiochem.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Aggrecanase degradation of type III collagen is associated with clinical knee pain

Abstract: There is a lack of biochemical markers for non-invasive and objective assessment of symptomatic osteoarthritis (OA). Aggrecanase activity has been shown to be associated with joint deterioration and symptomatic disease through the degradation of extracellular matrix proteins, such as type III collagen. Our study aimed to identify and develop a novel biomarker by measuring an aggrecanase-mediated type III collagen neoepitope, and correlate levels of this biomarker with OA joint pain. Mass spectrometric analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…These results are similar to previous results. Bay-Jensen reported that serum COL3/ ADAMTS was weakly associated with pain scores (r = − 0.13-0.17, p < 0.05) [44]. Sun compared MMP-3 and NRS but did not find any correlation [45].…”
Section: Discussionmentioning
confidence: 91%
“…These results are similar to previous results. Bay-Jensen reported that serum COL3/ ADAMTS was weakly associated with pain scores (r = − 0.13-0.17, p < 0.05) [44]. Sun compared MMP-3 and NRS but did not find any correlation [45].…”
Section: Discussionmentioning
confidence: 91%
“…In the 10 core genes, increased mRNA expression levels of COL1A1, COL1A2, COL2A1, COL3A1, COL5A2 genes have been reported in OA (Bay-Jensen et al, 2018; Jin et al, 2009; Karlsson et al, 2010; Hermansson et al, 2004). Studies have shown that increased secretion of type I collagen encoded by COL1A1 and COL1A2 homotrimers in OA can induce stenosis and unorganized collagen fibers in subchondral bone (Clements et al, 2009; Couchourel et al, 2009; Jin et al, 2009; Steinberg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Type III collagen encoded by COL3A1, together with type I collagen, provides a structural framework for the synovium surrounding the synovial joint (Hu et al, 2017; Reichert et al, 2018). Upregulation of type III in OA leads to thickening of the synovial membrane and has potential as a biomarker for OA (Bay-Jensen et al, 2018). Type V collagen encoded by COL5A1 and COL5A2, as a member of group I collagen, is present in tissues containing type I collagen, and appears to regulate the assembly of shaped fibers composed of type I and type V collagen (Colombi et al, 2017; Willard et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to aggrecan, ADAMTS4 can also cleave collagen type III. Ex vivo cultures indicate that most of the ADAMTS activity toward collagen type III cleavage is exerted by ADAMTS4 produced in the synovium and not in the cartilage, 232 suggesting a significant contribution of inflammatory cytokine‐activated synovial cells to ADAMTS expression and collagen breakdown. Degradative enzyme expression associated with OA synovial fibrosis pathogenesis are likely to promote other joint tissue destructive processes as a result of FLS responses to inflammatory and fibrotic signaling molecules.…”
Section: Inflammatory Fibroblast Dysfunctions: a Closer View Into The Synoviummentioning
confidence: 99%